Extending the operation of a solar air collector to night-time by integrating radiative sky cooling: A comparative experimental study. (15th July 2022) - Hu, Mingke; Zhao, Bin; Suhendri,; Cao, Jingyu; Wang, Qiliang; Riffat, Saffa; Su, Yuehong; Pei, Gang
Abstract: Solar thermal collectors are generally unproductivity at night without sunlight. Radiative cooling, on the other hand, is another renewable technology harvesting coldness from extraterrestrial space and can effectively work nocturnally. Therefore, this study proposes a scheme that integrates the nocturnal radiative cooling mechanism into a solar air collector as a supplementary. Incoming air is heated by the solar absorber during the daytime and cooled down by the glass cover at night. Experimental results indicate that, with an air mass flow rate of 0.03 kg/s, the dual-mode collector (named as PT-RC collector) realized a daytime solar thermal efficiency of 34.2% at zero-reduced temperature (e.g., when the inlet air temperature equals the ambient temperature) and a net radiative cooling power (e.g., when the inlet air temperature equals the ambient temperature) of 27.9 W/m 2, which are 72.2% and 2.4 times those of the typical solar air collector. As the air mass flow rate increased from 0.01 to 0.05 kg/s, the two performance indicators lifted from 19.8% to 34.5% and from 16.9 to 33.0 W/m 2, respectively. The PT-RC collector shows potential to be applied in four-season regions where heating and cooling are both required throughout the year or tropical zones where cooling is much more desired. Highlights: A new design to extend the operation of a solar air collector to nighttime. A solar thermal efficiency over 70% of that of the typical solar air heater. An average cooling power about three times that of the typical solar air heater. Cooling power lifts to 33.0 W/m 2 as the mass flow rate increases to 0.05 kg/s.